2020
DOI: 10.1371/journal.pone.0239002
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing sensitivity and culturally modified resilience education: Differential susceptibility in Japanese adolescents

Abstract: This study investigated the efficacy of a culturally modified resilience education program on Japanese adolescents’ well-being from a differential susceptibility perspective. First, a culturally modified resilience education intervention was developed by employing the SPARK resilience program and implemented with 407 Japanese high school students in Tokyo (age = 15–16, M = 192, F = 215). To test intervention efficacy, students’ level of resilience, self-esteem, self-efficacy, and depression were measured pre-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 54 publications
4
26
0
2
Order By: Relevance
“…This study performed a series of quantitative text analyses and provided findings regarding effective coping strategies for better mental health in low-, medium-, and high-SPS university students. The results support the existing evidence that individual differences in SPS should be considered when constructing a school-based and universally designed intervention program (Kibe et al, 2020;Pluess & Boniwell, 2015;Yano et al, 2020a). In practice or in applied research, programs considering the characteristics of each sensitivity group could more effectively improve mental health than those that are universally designed, which are traditionally conducted.…”
Section: Strengths Limitations and Future Directionssupporting
confidence: 76%
See 1 more Smart Citation
“…This study performed a series of quantitative text analyses and provided findings regarding effective coping strategies for better mental health in low-, medium-, and high-SPS university students. The results support the existing evidence that individual differences in SPS should be considered when constructing a school-based and universally designed intervention program (Kibe et al, 2020;Pluess & Boniwell, 2015;Yano et al, 2020a). In practice or in applied research, programs considering the characteristics of each sensitivity group could more effectively improve mental health than those that are universally designed, which are traditionally conducted.…”
Section: Strengths Limitations and Future Directionssupporting
confidence: 76%
“…In applied work, SPS has been shown to moderate the beneficial effects of psychological intervention programs. For instance, highly sensitive adolescents had lower depressive tendencies (Pluess & Boniwell, 2015) or higher self-esteem (Kibe, Suzuki, Hirano, & Boniwell, 2020) than others after a school-based resilience program. Similarly, psychoeducational or physical exercise (i.e., yoga) programs implemented in educational institutions may have more beneficial effects for high-SPS students than low-SPS students, such as infrequent maladaptive behavior (Nocentini, Menesini, & Pluess, 2018) or a low level of anxiety (Amemiya et al, 2020).…”
Section: Sensory Processing Sensitivity As a Moderator Of Psychological Interventionsmentioning
confidence: 99%
“…In contrast, individuals with low sensitivity are less likely to be affected by positive experiences (i.e., Vantage Resistance). Indeed, several studies examining the effects of positive psychological interventions have demonstrated that highly sensitive individuals benefited more from interventions than low-sensitivity individuals (Kibe et al, 2020;Nocentini et al, 2018;Pluess & Boniwell, 2015). If our newly created HSP-J10 is a validated measure to assess sensitivity, it is expected to moderate the relationship between positive experiences and their consequences, as in previous works.…”
Section: Studymentioning
confidence: 75%
“…More recently, it has been confirmed that Environmental Sensitivity also moderates the positive effects of a supportive environment (e.g., Iimura & Kibe, 2020;Kibe et al, 2020;Nocentini et al, 2018;Pluess & Boniwell, 2015). For example, highly sensitive children are more likely to benefit (e.g., lower depression and anxiety) from school-based positive psychological interventions (e.g., resilience training and bullying prevention interventions), which is called Vantage Sensitivity.…”
Section: Highly Sensitive Personmentioning
confidence: 98%
“…As for the country of origin, three of the studies were conducted in Japan [10,12,17], two in United States [9,15], and other two in United Kingdom [14,19]. One article was carried out in each of the following countries: Malaysia, Sweden, Denmark, Iran, Israel and China [11,13,16,18,20,21].…”
Section: Description Data and Types Of Studiesmentioning
confidence: 99%